Ex Vivo Liver Resection and Autotransplantation: Should It be Used More Frequently?. Issue 5 (2nd November 2022) - Weiner, Joshua; Hemming, Alan; Levi, David; Beduschi, Thiago; Matsumoto, Rei; Mathur, Abhishek; Liou, Peter; Griesemer, Adam; Samstein, Benjamin; Cherqui, Daniel; Emond, Jean; Kato, Tomoaki
Abstract : Objective: We herein advocate for more extensive utilization of ex vivo resection techniques for otherwise unresectable liver tumors by presenting the largest collective American experience. Background: Advanced in situ resection and vascular reconstruction techniques have made R0 resection possible for otherwise unresectable liver tumors. Ex vivo liver resection may further expand the limits of resectability but remains underutilized due to concerns about technical complexity and vascular thrombosis. However, we believe that the skillset required for ex vivo liver resection is more widespread and the complications less severe than widely assumed, making ex vivo resection a more attractive option in selected case. Methods: We retrospectively analyzed 35 cases performed by surgical teams experienced with ex vivo liver resections (at least 4 cases) between 1997 and 2021. Results: We categorized malignancies as highly aggressive (n=18), moderately aggressive (n=14), and low grade (n=3). All patients underwent total hepatectomy, vascular reconstruction and resection in hypothermia on the backtable, and partial liver autotransplantation. Overall survival was 67%/39%/28%, at 1/3/5 years, respectively, with a median survival of 710 days (range: 22–4824). Patient survival for highly aggressive, moderately aggressive, and low-grade tumors was 61%/33%/23%, 67%/40%/22%, and 100%/100%/100% at 1/3/5 years, respectively, with median survival 577 days (range: 22–3873), 444 days (range: 22–4824), and 1825 days (range: 868–3549). Conclusions: Ex vivo resection utilizes techniques commonly practiced in partial liver transplantation, and we demonstrate relatively favorable outcomes in our large collective experience. Therefore, we propose that more liberal use of this technique may benefit selected patients in centers experienced with partial liver transplantation.